2020
DOI: 10.1002/pssa.201900590
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Electronic Properties of Tin Carbide Nanowires

Abstract: Herein, the mechanical and electronic properties of tin carbide nanowires (NWs) with zinc‐blende structure are theoretically investigated using density functional calculations within the generalized gradient approximation. The axes of the studied NWs, which have hexagonal cross sections of six different sizes, are taken along the [111] crystallographic direction, and their surfaces are passivated with either hydrogen or fluorine. The effects of diameter size and chemical passivation on the cohesive energy, ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
0
0
Order By: Relevance
“…In conclusion, the current Young's modulus results for SWGeCNTs and SWSnCNTs were compared with those reported for GeC and SnC nanowires (NWs) by Salazar and Pérez [48], and Marcos-Viquez et al [49], respectively, as shown in Figure 15. Salazar and Pérez [48] evaluated the Young's modulus of the GeCNWs with a diamond structure, implementing DFT within the local density approximation (LDA) in the SIESTA code.…”
Section: Young's Modulus Of Single-walled Gecnts and Sncntsmentioning
confidence: 79%
See 1 more Smart Citation
“…In conclusion, the current Young's modulus results for SWGeCNTs and SWSnCNTs were compared with those reported for GeC and SnC nanowires (NWs) by Salazar and Pérez [48], and Marcos-Viquez et al [49], respectively, as shown in Figure 15. Salazar and Pérez [48] evaluated the Young's modulus of the GeCNWs with a diamond structure, implementing DFT within the local density approximation (LDA) in the SIESTA code.…”
Section: Young's Modulus Of Single-walled Gecnts and Sncntsmentioning
confidence: 79%
“…Salazar and Pérez [48] evaluated the Young's modulus of the GeCNWs with a diamond structure, implementing DFT within the local density approximation (LDA) in the SIESTA code. Marcos-Viquez et al [49] employed the same modelling approach with the difference of using the general gradient approximation (GGA) instead of the LDA, to assess the Young's modulus of the SnCNWs with a zinc blende structure. The values of E for the SWGeCNTs and SWSnCNTs were calculated by Equation ( 23), with t n = 0.381 nm and 0.387 nm, respectively.…”
Section: Young's Modulus Of Single-walled Gecnts and Sncntsmentioning
confidence: 99%